2016
DOI: 10.2352/issn.2470-1173.2016.2.vipc-228
|View full text |Cite
|
Sign up to set email alerts
|

Guided Filter Demosaicking For Fourier Spectral Filter Array

Abstract: We recently introduced a spectral filter array design for single-shot multispectral imaging that is based on Fourier transform spectroscopy. In this article, we investigate feasibility of guided filter demosaicking for our SFA design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…(ii) The considered MSFA has already been realized in hardware as a prototype sensor [ 7 ]. (iii) Jia et al have also used the same MSFA arrangement and have reported its effectiveness by the frequency domain analysis of the MSFA [ 67 , 68 ]. These facts suggest the potential of the considered MSFA.…”
Section: Related Workmentioning
confidence: 99%
“…(ii) The considered MSFA has already been realized in hardware as a prototype sensor [ 7 ]. (iii) Jia et al have also used the same MSFA arrangement and have reported its effectiveness by the frequency domain analysis of the MSFA [ 67 , 68 ]. These facts suggest the potential of the considered MSFA.…”
Section: Related Workmentioning
confidence: 99%
“…51,52 Compressive sensing to compensate for the increasing sparsity have also been used successfully. [53][54][55] Specific to technology, such as Fourier SFA 56,57 and hybrid multi-camera approaches 58 and specific to application demosaicing 59 have also been developed.…”
Section: Introductionmentioning
confidence: 99%